Whole heart action potential duration restitution properties in cardiac patients: a combined clinical and modelling study. - Nash, M; Bradley, C; Sutton, P; Clayton, R; Kallis, P; Hayward, M; Paterson, D; Taggart, P (2006)
Steep action potential duration (APD) restitution has been shown to facilitate wavebreak and ventricular fibrillation. The global APD restitution properties in cardiac patients are unknown. We report a combined clinical electrophysiology and computer modelling study to: (1) determine global APD restitution properties in cardiac patients; and (2) examine the interaction of the observed APD restitution with known arrhythmia mechanisms. In 14 patients aged 52-85 years undergoing routine cardiac surgery, 256 electrode epicardial mapping was performed. Activation-recovery intervals (ARI; a surrogate for APD) were recorded over the entire ventricular surface. Mono-exponential restitution curves were constructed for each electrode site using a standard S1-S2 pacing protocol. The median maximum restitution slope was 0.91, with 27% of all electrode sites with slopes<0.5, 29% between 0.5 and 1.0, and 20% between 1.0 and 1.5. Eleven per cent of restitution curves maintained slope>1 over a range of diastolic intervals of at least 30 ms; and 0.3% for at least 50 ms. Activation-recovery interval restitution was spatially heterogeneous, showing regional organization with multiple discrete areas of steep and shallow slope. We used a simplified computer model of 2-D cardiac tissue to investigate how heterogeneous APD restitution can influence vulnerability to, and stability of re-entry. Our model showed that heterogeneity of restitution can act as a potent arrhythmogenic substrate, as well as influencing the stability of re-entrant arrhythmias. Global epicardial mapping in humans showed that APD restitution slopes were organized into regions of shallow and steep slopes. This heterogeneous organization of restitution may provide a substrate for arrhythmia.